Colonic malakoplakia in a liver transplant recipient: A case report - Rana Ajabnoor; Mohammad Mawardi; Abdulmonem Almutawa (Elsevier, 2019)
Malakoplakia is an unusual chronic inflammatory condition that commonly occurs as a complication in immunocompromised patients. It is associated with bacterial infection, specifically Escherichia coli. Gastrointestinal malakoplakia in patients with organ transplant has rarely been described in the literature. We report the case of a 55-year-old male patient who had an orthotropic liver transplant 2 years before presentation and had been taking a combination of tacrolimus and prednisolone. He reported chronic watery diarrhea for the previous 6 months with no history of infection. His colonoscopy showed diffuse multiple mucosal nodules and ulcers appearing in the rectum and throughout the colon. A colonic biopsy revealed infiltration of the lamina propria by chronic inflammatory cells and sheets of histiocytes with the inclusion of Michaelis-Gutmann bodies. Pathological findings were consistent with malakoplakia. This is the sixth reported case of this presentation worldwide. Clinicians should be aware of this disease with its diverse pattern of presentation, as it can be a potential cause of diarrhea in liver transplant recipients. It is crucial to differentiate the pathology associated with this disease from that of other causes because it is a self-limited condition that can be managed well by prescribing antibiotics and reducing immunosuppression therapy. Keywords: Colonic malakoplakia, Immunocompromised, Liver transplant, Michaelis-Gutmann